Current status of calcitonin gene-related peptide-based therapies in migraine: a scoping review - Ahsan, Marya; Mallick, Ayaz Khurram (International Journal of Basic & Clinical Pharmacology, 2022)
A significant proportion of patients exhibit sub-optimal response to the standard treatment of acute migraine such as triptans and NSAIDs. Even the conventional preventive therapies (e.g. beta-blockers) indicated for patients with frequent migraine attacks have varying responses. Moreover, evidence from animal studies elucidated the role of calcitonin gene-related peptide (CGRP) in the pathophysiology of migraine. Currently two classes are drug, the small molecule CGRP receptor antagonist or the ‘gepants’ (Ubrogepant, Rimegepant, Atogepant, Zavegepant) and CGRP monoclonal antibodies (Erenumab, Galcanezumab, Fremanezumab, Eptinezumab) have been found efficacious and safe in various clinical trials for the treatment and prevention of migraine. While the small molecule CGRP receptor antagonists are given orally, the monoclonal antibodies are injectable drugs. Ubrogepant and Rimegepant are the second-generation gepants approved for treatment of migraine. Zavegepant is a third generation gepant which has proven efficacy for acute treatment of migraine in a phase III trial. Atogepant has been approved for prevention of migraine. Rimegepant has also proven to be efficacious for preventing migraine attacks but has not yet been approved for this indication. Erenumab is the only monoclonal antibody which neutralizes the CGRP receptor. The latter three monoclonal antibodies target the CGRP peptide. The monoclonal antibodies have been approved for the prevention of migraine as a subcutaneously or intravenous infusion (Eptinezumab) given once a month or quarterly. Both the classes of drugs were well-tolerated in the clinical trials. Nausea was the most common adverse effect with gepants while injection-site pain was commonly reported with the antibodies.